An rTMS study into self-face recognition using video-morphing technique - Heinisch, Christine; Dinse, Hubert; Tegenthoff, Martin; Juckel, Georg; Brüne, Martin (Social cognitive and affective neuroscience, 2011)

Attachment behavior and correlations to alpha-asymmetry in foster children and children with their biological family - Heinisch, Christine; Bovenschen, Ina; Kungl, Melanie; Spangler, Gottfried; Ries, C. (23. Kongress International Society for the Study of Behavioral Development (ISSBD), 2014)

Attachment Representation as a Moderator between Emotion Perception and Information Processing - Heinisch, Christine; Leyh, Rainer; Spangler, Gottfried (Frontiers in Human Neuroscience, 2016)

Attachment Representation Moderates the Influence of Emotional Context on Information Processing - Leyh, Rainer; Heinisch, Christine; Kungl, Melanie; Spangler, Gottfried (Frontiers in Human Neuroscience, 2016)

Blind subjects are unaware of changes in hand asymmetry - Heinisch, Christine; Dinse, Hubert (9th International Multisensory Research Forum, 2008)

Deactivating attachment strategies associate with early processing of facial emotion and familiarity in middle childhood: an ERP study - Kungl, Melanie; Vrticka, Pascal; Heinisch, Christine; Beckmann, Matthias; Fasching, Peter; Ziegler, Clara; Spangler, Gottfried (Attachment and Human Development, 2022)
Neurophysiological evidence suggests associations between attachment and the neural processing of emotion expressions. This study asks whether this relationship is also evident in middle childhood, and how it is affected by facial familiarity. Attachment strategies (deactivation, hyperactivation) were assessed in 51 9- to 11-year olds using a story stem completion task. Event-related potentials (ERPs) were recorded during children's passive viewing of mother and stranger emotional faces (angry/happy). At the stage of facial information encoding (N250), attachment deactivation was associated with a pattern pointing to increased vigilance towards angry faces. Further, the attention-driven LPP was increased to happy mother faces as highly salient stimuli overall, but not in children scoring high on deactivation. These children did not discriminate between mothers' facial emotions and showed a general attentional withdrawal from facial stimuli. While our results on attachment deactivation support a two-stage processing model, no effect of hyperactivation was found.
CRIS-Team WoS Importer:2022-10-21

Does anxiety impact the neural processing of child faces in mothers of school-aged children? An ERP study using an emotional Go/NoGo task - Kungl, Melanie; Rutherford, Helena J.V.; Heinisch, Christine; Beckmann, Matthias; Fasching, Peter; Spangler, Gottfried (Social Neuroscience, 2020)
Maternal anxiety during pregnancy and the early postpartum period is associated with heightened neural processing of neutral infant faces as measured by event-related potentials (ERPs). However, less is known about how anxiety shapes neural face processing in mothers of older children. In our study, 36 mothers of 8–10 year old children completed a Go/NoGo task consisting of neutral and emotional (happy, fearful) facial expressions posed by unfamiliar school-aged children while EEG was recorded. Higher levels of maternal anxiety -indexed via self-report- were associated with delayed behavioral responses to children’s fearful faces and increased N170 and LPP amplitudes elicited by children’s neutral faces. While anxiety was also positively related to the LPP elicited by children’s emotional faces, it only led to increased N170 amplitude responses to children’s fearful, but not happy, faces and only when they were NoGo cues. The study replicates and extends prior findings examining the impact of maternal anxiety on neural responses to neutral infant faces to later stages of parenting with further neural markers and emotional expressions being affected. Findings evidence the importance of studying these associations beyond infancy to increase our knowledge about processes potentially underlying the relation between anxiety and less optimal parenting across development.
CRIS-Team Scopus Importer:2020-07-24
Keywords: EEG/ERP; emotional faces; Go/NoGo task; LPP; Maternal anxiety; N170

Emotional Context Effects on the Rating of Ambiguous Facial Expressions in Depression and Schizophrenia Spectrum Disorders - Kramer, Marco; Stetter, Martina; Heinisch, Christine; Baumgart, Patrick; Brüne, Martin; Mavrogiorgou, Paraskevi; Juckel, Georg (Psychiatry-Interpersonal and Biological Processes, 2024)
Objective: To investigate the influence of visual contextual information on emotion recognition of ambiguous facial expressions in depression and schizophrenia spectrum disorders. Method: Ambiguous facial expressions and emotional contexts representing anger, disgust, fear, joy, sadness and surprise were validated in a pre-test with healthy independent raters. Afterwards, 20 healthy participants (8 women, 12 men; mean age 24.35 ± 2.85 years), 20 participants with schizophrenia spectrum disorders (9 women, 11 men; mean age 40.25 ± 11.68 years) and 19 participants with depression (11 women, 8 men; mean age 43.74 ± 12.65 years) rated the emotional content of nine different faces in seven different emotion-suggesting contexts. The proportions of context-congruent answers and differences between emotion ratings in each context were analysed using non-parametric Kruskal-Wallis and explorative, paired Wilcoxon tests. Correlational analyses explored the influence of clinical symptoms assessed by clinician-administered scales. Results: The overall proportion of context-congruent answers did not differ between participants with depression and schizophrenia spectrum disorders compared to healthy participants. Participants with schizophrenia spectrum disorders were more susceptible to anger-suggesting contexts and participants with depression were more susceptible to fear-suggesting contexts. Differences in emotion recognition were associated with the severity of depressive, but not psychotic, symptoms. Conclusion: Despite increased susceptibility to anger-suggesting cues in schizophrenia and to fear-suggesting cues in depression, visual contextual influence remains largely consistent with healthy participants. Preserved emotional responsiveness suggests an efficacy of emotion training but emphasizes the need for additional research focusing on other factors contributing to social interaction deficits.
CRIS-Team Scopus Importer:2024-01-26

Empathy moderates the effect of repetitive transcranial magnetic stimulation of the right dorsolateral prefrontal cortex on costly punishment - Brüne, Martin; Scheele, Dirk; Heinisch, Christine; Tas, Cumhur; Wischniewski, Julia; Güntürkün, Onur (PLoS ONE, 2012)

Facial expressions in Schizophrenia - Heinisch, Christine (Brainreading & Neuroethics: Understanding Persons, 2011)

Hypnotic ingroup-outgroup suggestion influences economic decision-making in an Ultimum Game - Brüne, Martin; Tas, Cumhur; Wischniewski, Julia; Welpinghus, Anna; Heinisch, Christine; Newen, Albert (Consciousness and cognition, 2012)

Infants' attention is biased by emotional expressions and eye gaze direction - Heinisch, Christine; Höhl, Stefanie; Palumbo, Letizia; Striano, Tricia (NeuroReport, 2008)

Maternal attachment representation and neurophysiological processing during the perception of infants' emotional expressions - Leyh, Rainer; Heinisch, Christine; Behringer, Johanna; Spangler, Gottfried (PLoS ONE, 2016)

Mütterliche Bindungsrepräsentation und Neurophysiologische Verarbeitung kindlicher Emotionsausdrücke - Heinisch, Christine (Deutsche Gesellschaft für Psychologie, 2014)
Leitung der Arbeitsgruppe "Entwicklung sozialer Fertigkeiten"

Mütterliche Feinfühligkeit bei postpartalen Depressionen und Angststörungen - Heinisch, Christine (Tagung der Marcé-Gesellschaft, 2017)

Recognition and generation of emotional expressions in Schizophrenia - Heinisch, Christine (Interdisciplinary Conference "Other Minds - Embodied Interaction and Higher Order Reasoning", 2011)

Repetitive transcranial magnetic stimulation over the temporo-parietal junction influences distinction of self from famous but not unfamiliar others - Heinisch, Christine; Krüger, M.; Brüne, Martin (Behavioral neuroscience, 2012)

Sage in press - Ageing and Touch - Heinisch, Christine; Dinse, Hubert; Tegenthoff, Martin; Kalisch, Tobias (The Sage Encyclopedia of Perception, 2008)

Self-face recognition in schizophrenia is related to inside - Heinisch, Christine; Stefan, Wiens; Gründl, Martin; Juckel, Georg; et al. (European archives of psychiatry and clinical neuroscience, 2013)

Self-face recognition is related to higher order self-awareness in schizophrenic patients - Heinisch, Christine (Workshop "The Social Brain", 2011)

Self-face recognition is related to higher order self-awareness in schizophrenic patients - Heinisch, Christine; Brüne, Martin; Juckel, G; Stefan, Wiens (Journal of Neuropsychiatry and Clinical Neurosciences, 2013)

Self-other discrimination in schizophrenia is associated with awareness of illness - Heinisch, Christine; Brüne, Martin (Robert Sommer Symposium, 2010)

Self-Other discrimination in schizophrenic patients - Heinisch, Christine; Brüne, Martin (Robert Sommer Award Symposium, 2008)

The cortical network of visual self-face recognition - Heinisch, Christine; Dinse, Hubert; Brüne, Martin (2nd Schizophrenia International Research Society Conference, 2010)

Visual self-face recognition in schizophrenic patients - Heinisch, Christine; Brüne, Martin (9th World Congress of Biological Psychiatry, 2009)